Exploratory Research on Carbon Emission Accounting and Reduction Strategies for University Campuses in Severe Cold Zones of China - Yangyang Wang; Weiya Chen; Weijia Chen; Qingying Hou (Buildings)
In this study, the carbon emissions of Jilin University of Architecture and Technology were comprehensively calculated using the “Guidelines for accounting of carbon emissions of university campuses” issued by the China Association for Energy Conservation in Buildings. The total emissions for 2023 amounted to 13,571.85 tonnes of CO2 equivalents, with a per person emission of 0.93 tonnes. Incorporating carbon offsets like green plant sequestration, renewable energy, and waste recycling reduced emissions by 9007.68 tonnes, resulting in a net emission of 4564.17 tonnes and a per person net emission of 0.31 tonnes. To further cut emissions, the university implemented strategies such as nearly zero-energy buildings, clean energy heating, energy monitoring, and green courses. Despite these efforts, achieving carbon neutrality remains challenging. The university could explore opportunities to increase renewable energy use or procure green electricity. Its adoption of clean electricity for heating in the severe cold zones not only supports carbon neutrality but also serves as a model for similar campuses.